Iron Chelator Deferoxamine Alleviates Progression of Diabetic Nephropathy by Relieving Inflammation and Fibrosis in Rats - Yunfei Feng; Li Jia; Wan Ma; Chenying Tian; Huahua Du (Biomolecules, 2023)
Diabetic nephropathy (DN) is one of the most devastating diabetic microvascular complications. It has previously been observed that iron metabolism levels are abnormal in diabetic patients. However, the mechanism by which iron metabolism levels affect DN is poorly understood. This study was designed to evaluate the role of iron-chelator deferoxamine (DFO) in the improvement of DN. Here, we established a DN rat model induced by diets high in carbohydrates and fat and streptozotocin (STZ) injection. Our data demonstrated that DFO treatment for three weeks greatly attenuated renal dysfunction as evidenced by decreased levels of urinary albumin, blood urea nitrogen, and serum creatinine, which were elevated in DN rats. Histopathological observations showed that DFO treatment improved the renal structures of DN rats and preserved podocyte integrity by preventing the decrease of transcripts of nephrin and podocin. In addition, DFO treatment reduced the overexpression of fibronectin 1, collagen I, IL-1β, NF-κB, and MCP-1 in DN rats, as well as inflammatory cell infiltrates and collagenous fibrosis. Taken together, our findings unveiled that iron chelation via DFO injection had a protective impact on DN by alleviating inflammation and fibrosis, and that it could be a potential therapeutic strategy for DN.